Existence and Uniqueness of Equilibrium in Nonoptimal Unbounded Infinite Horizon Economies - Olivier F. Morand; Kevin L. Reffett (Tinbergen Institute, 2002)
In applied work in macroeconomics and finance, nonoptimal infinite horizon economies are often studied in which the state-space is unbounded. Important examples of such economies are single-sector growth models with production externalities, valued fiat money, monopolistic competition, and/or distortionary government taxation. Although sufficient conditions for existence and uniqueness of Markovian equilibrium are weIl known for the compact state space case, no similar sufficient conditions exist for unbounded growth. This paper provides such a set of sufficient conditions, and presents a computational algorithm that will prove asymptotically consistent when computing Markovian equilibrium.
Keywords: C62; D58; D62; 330; Equilibrium; Dynamic Models; Unbounded; Nonoptimal; Dynamisches Modell; Gleichgewicht